(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2015)
Antibiotics form an intergral part in the management of odontogenic infections. Streptococci group of bacteria have been implicated as one of the important causative agents in dental caries and dental abscess. The objective of this study was to determine the sensitivity and resistance of pathogenic facultative anaerobic streptococci to various routinely used antibiotics in odontogenic infections and also to determine appropriate empirical antibiotic therapy for the orofacial infections of odontogenic origin. Primary culture was performed for duration of 48 hours with the samples obtained from the patient. A lawn culture from the primary culture was made and antibiotic sensitivity testing was done using commercially available antibiotic disks by disk diffusion method. Standard strain of Streptococcus mutans (MTCC 497) was subjected to susceptibility testing by the above mentioned method. Poor susceptibility was seen in amoxicillin (18.4%), amoxicillin clavulanic acid (14.3%), and erythromycin (26.5%). Maximum resistance was noted for metronidazole (89.8%). High susceptibility was observed in tetracycline (67.3%), streptomycin (61.2%) and ciprofloxacin (44.9%). Low resistance was also exhibited by gentamycin (22.4%) and doxycycline (40.8%). Streptococcus mutans (MTCC 497) too showed similar results as that of the test samples. Due to the evolving resistance to all major antimicrobial agents used for treatment of odontogenic infections, antibiotic susceptibility testing is important to direct therapy. Antimicrobial susceptibility helps in monitoring the changing patterns of resistance and can be useful for empirical treatment of odontogenic infections.